X x 1999 - x = 1999 x 1997 + 1999
X x (1999 - 1) = 1999 x (1997 + 1)
X x 1998 = 1999 x 1998
Vậy x = 1999
Đúng 0
Bình luận (0)
X x 1999 - x = 1999 x 1997 + 1999
X x (1999 - 1) = 1999 x (1997 + 1)
X x 1998 = 1999 x 1998
Vậy x = 1999
X x 1999 - x = 1999 x 1997 + 1999
x nhân 1999--x=1999 nhan 1997+1999
Tìm X bằng cách hợp lí nhất X × 1999 × X = 1999 × 1997 + 1999
tìm x biết:
a) 5 *x - 1952 = 2500 - 1947
b) x *1999 - x =1999 *1997+ 1999
X x 1999 - x = 1999 x 1997 + 1999
Ai trả lời thì trình bày nha, ai không trình bày coi như tính sai
1996 x 1997 + 1998 x 3 + 1994 / 1997 x 1999 - 1997 x 1997
tìm x biết:
x*1999 -x=1999*1997+1999
tìm x biết:
x*1999 -x=1999*1997+1999
(1999 x 1998 + 1998 + 1997) x (1 + : 1
- 1
)